Students’ Perception on the Use of Web-Based Technology for Learning English Skills at University - Sri Wahyuni; Ekidito Briliawan Hakiki (ELITE JOURNAL, 2023)
This study aims to examine English Students’ perception toward the use of web-based technology for learning English skills at university level. The study employed survey research because it was conducted to investigate and describe the characteristic of the research subject. The research participant are from Semester 1 and 3 English students at IAIN Kediri in academic year 2020/2021 that consists of 345 students. For the sample, it took 50% from the whole students which are 172 students. Close-ended Questionnaire is used as the instrument of this study. The data obtained through five point of Likert scale survey and reported in percentage. The data collected were analyzed using descriptive statistic by finding out the total score per item. The results of this study shows that English students have positive perception of the use of web-based technology related to language skills (78% of students), behavioral (74% of students), and affective components (72% of students). Key words: Students’ perception, Web-based technology. English skill